Replication defective viral genomes exploit a cellular pro-survival mechanism to establish paramyxovirus persistence. Issue 1 (December 2017) - Xu, Jie; Sun, Yan; Li, Yize; Ruthel, Gordon; Weiss, Susan; Raj, Arjun; Beiting, Daniel; López, Carolina
Abstract Replication defective viral genomes (DVGs) generated during virus replication are the primary triggers of antiviral immunity in many RNA virus infections. However, DVGs can also facilitate viral persistence. Why and how these two opposing functions of DVGs are achieved remain unknown. Here we report that during Sendai and respiratory syncytial virus infections DVGs selectively protect a subpopulation of cells from death, thereby promoting the establishment of persistent infections. We find that during Sendai virus infection this phenotype results from DVGs stimulating a mitochondrial antiviral-signaling (MAVS)-mediated TNF response that drives apoptosis of highly infected cells while extending the survival of cells enriched in DVGs. The pro-survival effect of TNF depends on the activity of the TNFR2/TRAF1 pathway that is regulated by MAVS signaling. These results identify TNF as a pivotal factor in determining cell fate during a viral infection and delineate a MAVS/TNFR2-mediated mechanism that drives the persistence of otherwise acute viruses. Replication defective viral genomes (DVGs) can facilitate persistence of paramyxoviruses, but the underlying mechanisms are unclear. Using FISH, Xu et al. here analyze the cellular response to DVGs on a single cell level and show that a MAVS-mediated TNF response specifically extends survival of cells enriched in DVGs.